Analysis of Profitability Ratios in Cigarette Companies Listed on the Indonesia Stock Exchange (2019-2021) - Nanan Sunandar; Imam Setia Permana (Budapest International Research and Critics University, 2023)
The financial condition of a company is the most important thing, so it needs effort in analyzing company finances. One way to do this is to analyze the company's financial statements. The profitability ratio is a calculation that is carried out to find out the state/financial condition of a company. The purpose of this study is to find out the evaluation findings of Net Profit Margin, Return on Assets, and Return on Equity in measuring the financial performance of cigarette sub-sector companies listed on the Indonesia Stock Exchange in 2019–2021. The method of analysis used was to measure the profitability ratios of each cigarette company studied. The results of an analysis of the financial statements and graphic images of four cigarette companies for the three year period 2019-2021 show that PT. HM Sampoerna has a better and more stable financial performance, where the average value of GPM = 21.31%, NPM = 29.44%, ROA = 25.19%, ROE = 30.37%. Meanwhile, PT Bentoel Internasional Investama Tbk has the worst financial performance, where the average GPM = 11.42%, NPM = (-18.86%), ROA = (-6.82%), ROE = (-15.33%). Gudang Garam Tbk can be said to have experienced fluctuating developments where the average value of GPM = 15.74%, NPM = 21.01%, ROA = 12.91%, ROE = 14.63%. Meanwhile PT. Wismilak Inti Makmur Tbk has GPM = 28.72%, NPM = 17.08%, ROA = 10.20%, ROE = 10.20%. From the four companies seen from the condition of their financial performance, PT. HM Sampoerna can be said to be better and more stable, compared to Gudang Faram Tbk, PT. Bentoel Internasional Investama Tbk and PT. Wismilak Inti Makmur Tbk.